Nurses Experience In Providing Care To COVID-19 Patients In Tasikmalaya, Indonesia - Tetik Nurhayati; Arip Rahman; Asep Riyana; Dewi Aryanti (Jurnal Keperawatan Respati Yogyakarta, 2023)
Nurses have challenges in caring for patients during Covid-19. This research contributed to identifying the experiences of nurses while caring for patients with Covid-19. This phenomenological qualitative research was done at Tasikmalaya in September–October 2021. The participants involved were the nurses who worked in a Covid-19 referral hospital. Among the participants involved, samples were selected purposively, obtaining 8 participants. Furthermore, data collection was carried out by in-depth interviews via Zoom meetings and observation. Data that have been collected were further analyzed using Creswell. As a result, four themes emerged, including the role of the nurse as a caregiver, procedures for handling COVID-19 patients, treatment provided for COVID-19 patients, and support from hospital management and families for the nurses. It was then summed up that the nurses are professional and fully responsible in providing nursing care while treating COVID-19 patients, although they are afraid and anxious of being contracted with COVID-19 patients. Conclusion This study provides an overview of the experiences of nurses when providing care to patients, motivation, among others, the obstacles experienced at work, support from those closest to them, and how participants adapt in providing care to patients with COVID-19 and then nurses are professional and fully responsible in providing nursing care while treating the Covid-19 patients. Nurses need support from other parties so that they can have strong motivation while providing nursing care.